Chinese and Global Burdens of Gastrointestinal Cancers From 1990 to 2019 - Xie, Wangcheng; Yang, Tingsong; Zuo, Jieliang; Ma, Zhilong; Yu, Weidi; Hu, Zhengyu; Song, Zhenshun (Frontiers in Public Health, 2022)
Background Gastrointestinal (GI) cancers are an important component of the tumor. This study aimed to investigate the burden of six major GI cancers in China and globally from 1990 to 2019. Methods We conducted a cross-sectional study based on the Global Burden of Disease Study (GBD) 2019. Indicators on incidence, deaths, disability-adjusted life-years (DALYs), and risk factors for esophageal, stomach, liver, pancreatic, colon and rectum, and gallbladder and biliary tract cancers were collected and analyzed for time trends. The contribution of each cancer and the proportion of cases in China among global cases were further reported. Results Global incidence cases, death cases, and DALYs of GI cancers showed an overall ascending trend over the past 30 years, but there was temporal and geographical variation across cancer types. By 2019, colon and rectum cancer had overtaken stomach cancer as the most burdensome GI cancer globally. However, stomach cancer narrowly continued to be the most burdensome GI in China. In addition, the proportion of incidence and death cases of stomach, pancreatic, colon and rectum, and gallbladder and biliary tract cancers among global cases had further increased. It was noteworthy that the burden of liver cancer in China has been alleviated significantly. Conclusion GI cancers remain a major public health problem in China and globally. Despite the temporal and geographic diversity of different cancers, targeted primary and secondary prevention are still necessary for the future to face these unknown challenges.